Insilico targeting of virus entry facilitator NRP1 to block SARS-CoV2 entry - Nousheen Bibi; Maleeha Shah; Shahzad Khan; Muhammad Shahzad Chohan; Mohammad Amjad Kamal (PLoS ONE, 2025)
The entry and infectivity of a virus are determined by its interaction with the host. SARS-CoV-2, the virus responsible for COVID-19, utilizes the spike (S) protein to attach to and enter host cells. Recent studies have identified neuropilin-1 (NRP1) as a crucial facilitator for the entry of SARS-CoV-2. The binding of the spike protein to the b1 domain of NRP1 has been shown to enhance viral infection twofold. Consequently, targeting NRP1 to disrupt this interaction represents a promising strategy to mitigate viral infection. In this study, a small molecule library of approximately 10,000 compounds was screened to identify those that could inhibit the interaction between NRP1 and the spike protein by targeting the b1 domain of NRP1. The crystallographic structure of the b1 domain of human NRP1 (PDB entry: 7JJC) was used for this purpose. Following virtual screening, docking studies, and evaluation of binding affinity and ADMET properties, 10 compounds were shortlisted. The top two candidates, AZD3839 and LY2090314, were selected for molecular dynamics simulation studies over 100 ns to assess binding stability. MM/GBSA calculations indicated that both AZD3839 and LY2090314 exhibited strong and stable binding to the b1 domain of NRP1. Computational modeling of the interaction between the b1 domain of NRP1 and the receptor-binding domain of the spike protein suggested that AZD3839 and LY2090314 could effectively hinder the NRP1-spike interaction. Therefore, these compounds may serve as potential drug candidates to reduce SARS-CoV-2 infectivity.